Long-term evaluation of the degradation behavior of three apatite-forming calcium phosphate cements - An, Jie; Liao, Hongbing; Kucko, Nathan W.; Herber, Ralf-Peter; Wolke, Joop G. C.; van den Beucken, Jeroen J. J. P.; Jansen, John A.; Leeuwenburgh, Sander C. G. (Journal of biomedical materials research. Part A, 2016)
Calcium phosphate cements (CPCs) are injectable bone substitutes with a long clinical history because of their biocompatibility and osteoconductivity. Nevertheless, their cohesion upon injection into perfused bone defects as well as their long‐term degradation behavior remain major clinical challenges. Therefore, the long‐term degradation behavior of two types of α‐tricalcium phosphate‐based, apatite‐forming CPCs was compared to a commercially available apatite‐forming cement, that is HydroSetTM. Carboxyl methylcellulose (CMC) was used as cohesion promotor to improve handling properties of the two experimental cements, whereas poly (d, l‐lactic‐co‐glycolic) acid (PLGA) microparticles were added to introduce macroporosity and stimulate CPC degradation. All three CPCs were injected into defects drilled into rabbit femoral condyles and explanted after 4, 12, or 26 weeks, after which the bone response was assessed both qualitatively and quantitatively. CPCs without PLGA microparticles degraded only at the periphery of the implants, while the residual CPC volume was close to 90%. On the contrary, bone ingrowth was observed not only at the periphery of the CPC, but also throughout the center of the implants after 26 weeks of implantation for the PLGA‐containing CPCs with a residual CPC volume of approximately 55%. In conclusion, it was shown that CPC containing CMC and PLGA was able to induce partial degradation of apatite‐forming CPCs and concomitant replacement by bone tissue. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1072–1081, 2016.